2011
DOI: 10.1002/hipo.20963
|View full text |Cite
|
Sign up to set email alerts
|

Septal elicitation of hippocampal theta rhythm did not repair cognitive and emotional deficits resulting from vestibular lesions

Abstract: Bilateral vestibular lesions cause atrophy of the hippocampus in humans and subsequent deficits in spatial memory and the processing of emotional stimuli in both rats and humans. Vestibular lesions also impair hippocampal theta rhythm in rats. The aim of the present study was to investigate whether restoring theta rhythm to the hippocampus of a rat, via stimulation of the medial septum, would repair the deficits caused by vestibular lesions. It was hypothesized that the restoration of theta would repair the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 47 publications
1
29
0
Order By: Relevance
“…Although the BVD animals were hyperactive, theta rhythm was abnormal across the entire range of movement velocities. These results have recently been replicated by Neo et al (2012), who tried but failed to reverse the spatial memory and emotional deficits caused by BVD by electrically stimulating the septum in order to provide an artificial theta rhythm. Tai et al (2012) also recently showed that rats that are administered sodium arsanilate intratympanically exhibit a reduction in theta power.…”
Section: Effects Of Vestibular Lesions On Head Direction Cell and Plamentioning
confidence: 74%
“…Although the BVD animals were hyperactive, theta rhythm was abnormal across the entire range of movement velocities. These results have recently been replicated by Neo et al (2012), who tried but failed to reverse the spatial memory and emotional deficits caused by BVD by electrically stimulating the septum in order to provide an artificial theta rhythm. Tai et al (2012) also recently showed that rats that are administered sodium arsanilate intratympanically exhibit a reduction in theta power.…”
Section: Effects Of Vestibular Lesions On Head Direction Cell and Plamentioning
confidence: 74%
“…In cats and dogs, passive translation does not increase the power but increases the peak frequency of theta (Arnolds et al, 1984). Moreover, vestibular lesions decrease the power and the frequency of theta (Russell et al, 2006; Neo et al, 2012; Tai et al, 2012). Nevertheless, restoration of theta in vestibular-deficient rats, by medial septum stimulation, is not sufficient to compensate for cognitive impairment induced by vestibular lesions (Neo et al, 2012).…”
Section: The Pathway From the Nucleus Reticularis Pontis Oralis To Tmentioning
confidence: 99%
“…This spatial memory impairment is likely to be related to hippocampal dysfunction, since both place cell responses (Stackman et al, 2002; Russell et al, 2003b) and theta rhythm have been reported to be abnormal (Russell et al, 2006; Neo et al, 2012; Tai et al, 2012; but see Stackman et al, 2002 for conflicting evidence regarding theta rhythm). On the other hand, CA1 and dentate gyrus (DG) field potentials and long-term potentiation (LTP) in vivo were not significantly affected by bilateral vestibular loss (Zheng et al, 2010a).…”
Section: Introductionmentioning
confidence: 99%